Structural change and the Kaldor facts in a growth model with relative price effects and non-Gorman preferences - Timo Boppart (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Growth is associated with (i) shifts in the sectoral structure of the economy, (ii) changes in relative prices and (iii) the Kaldor facts. Moreover, (iv) cross-sectional data shows systematic differences in the expenditure structure across income groups. This paper presents a growth model which is consistent with (i)-(iv) at the same time, a result the existing literature has not been able to generate. The theory is simple and parsimonious and contains an analytical solution. The model s functional form and cross-sectional data are exploited to estimate the relative importance of price and income effects as determinants of the structural change.
Keywords: O14; O41; D90; 330